Longitudinal white matter alterations in SIVmac239-infected rhesus monkeys with and without regular cART treatment - Liu, Jiaojiao; Nguchu, Benedictor Alexander; Liu, Dan; Qi, Yu; Aili, Xire; Han, Shuai; Gao, Yuxun; Wang, Xiaoxiao; Qiao, Hongwei; Cai, Chao; Huang, Xiaojie; Li, Hongjun (Frontiers in Immunology, 2023)
Objective: To use SIV-mac239-infected Chinese rhesus monkeys to study white matter changes with and without regular combined antiretroviral therapy (cART) and the relationships between the changes and clinical results. Methods: Diffusion tensor imaging (DTI) data were collected at baseline and 10 days, 4 weeks, 12 weeks, 24 weeks, and 36 weeks after viral inoculation. Plasma CD4 T cell counts, CD4/CD8 ratio, plasma viral load, and cerebrospinal fluid (CSF) viral load were collected at baseline and1 week, 5 weeks, 12 weeks , 24 weeks, and 36 weeks after viral inoculation. Microstructural characteristics were examined within 76 white matter areas defined by the DTI-white matter (WM) atlas for rhesus macaques. Corrections for multiple comparisons were performed using a false discovery rate (p < 0.05, FDR). Correlation analyzes between imaging markers and clinical markers (plasma CD4 T cell counts, CD4/CD8 ratio, plasma viral load, and cerebral spinal fluid viral load) were performed using Pearson correlations. Results: White matter changes in SIV-infected macaques were detected in different brain regions as early as 4 weeks after inoculation. As time progressed, cART reversed, ameliorated, or even enhanced the effects. The CD4 T cell count was mainly associated with DTI metrics before cART, while the CD4/CD8 ratio was associated with white matter changes with and without cART. Viral load was positively associated with mean diffusivity in HIV patients without cART, and the opposite results were seen in HIV patients with cART. Conclusion: SIV-mac239 infection may be an ideal tool for studying HIV-induced changes in the brain. The first white matter changes appeared in a structure adjacent to the periventricular area as early as 4 weeks after inoculation. As time progressed, cART had different effects on different regions, reversing, attenuating, or even progressing the pathology. Moreover, these changes were closely related to the CD4/CD8 ratio and viral load, even after cART.